Neocaeculus orientalis sp. nov. (Acari, Trombidiformes, Caeculidae) from Thailand - Fuangarworn, Marut; Butcher, Buntika Areekul (Zootaxa, 2015)
A new species of the predatory mite family Caeculidae, N. orientalis sp. nov., is described and illustrated, based on adult and all active immature instars from moss and forest litter of various localities in Thailand. Neocaeculus orientalis sp. nov. differs from its congeners in uniquely having the adult femur I divided but femora II–IV entire, adult coxal setation of 5-1-2-1 (4a excluded), and heterogeneous coxal setae. It is the first Neocaeculus species known to have no seta vi (= po) in all stages. A comparison of the diagnostic characters of known Neocaeculus species is given.